Effect of Kinetin Concentration on Callus Induction of Cryptocarya massoy (Oken) Kosterm Under in Vitro Conditions - Noli, Zozy Aneloi; Hanafi, Muhammad; idris, M.; Hany, Iga Permata (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The Papuan indigenous plant Cryptocarya massoy (Oken) Kosterm has substantial commercial significance as an essential oil source. Plant growth regulators (PGRs) are essential for regulating growth responses including callus development, and tissue culture offers a viable means of reproducing this species. Kinetin, a cytokinin-type PGR, is particularly important in promoting cell division and callus development. This study aimed to evaluate the growth response of C. massoy explants under varying kinetin concentrations and determine the optimal concentration for callus induction. The experiment utilized a Completely Randomized Design (CRD) with three kinetin treatments: 0.5 mg/L (A), 1.0 mg/L (B), and 1.5 mg/L (C). Results showed that 1.0 mg/L kinetin achieved the highest explant survival rate (71%) and the lowest browning rate (8%), compared to 13% browning at 0.5 mg/L and 1.5 mg/L. However, the highest callus formation (0.25 average callus) with a compact, brownish texture was observed at 1.5 mg/L. The 0.5 mg/L concentration consistently exhibited the lowest response across all parameters. These findings indicate that 1.0 mg/L kinetin is optimal for enhancing explant survival and minimizing browning, while 1.5 mg/L is more effective for inducing callus formation, underscoring the importance of kinetin concentration in optimizing C. massoy tissue culture protocols.